Development of Pedology as a Scientific Branch in the USA and Western Europe in the End of the XIX – Beginning of the XX Century: Source Study Aspect - Yanchenko, Tamara (Pedagogical Discourse, 2013)
The works on pedology, pedagogy and psychology, written in the USA and Western Europe in the end of the XIX – beginning of the XX century in the context of the defining their informational potential regarding studying features of pedology development have been characterized in the article. The author pays attention to the scientific heritage of J.Baldwin, W.James, W.Drummond, W.Lay, E.Meumann, W.Preyer, E.Thorndike, John Watson, S.Hall, A.Chamberlain, that is directly concerned with the origin and formation of pedology. The works contain important materials, allowing to explore the basic principles of pedology development and update its significance for education and upbringing of specified period of time.